Short-Physical Performance Battery (SPPB) score is associated with falls in older outpatients - Lauretani, Fulvio; Ticinesi, Andrea; Gionti, Luciano; Prati, Beatrice; Nouvenne, Antonio; Tana, Claudio; Meschi, Tiziana; Maggio, Marcello (Aging clinical and experimental research, 2019)
Background The capacity of Short-Physical Performance Battery (SPPB) test to discriminate between fallers and non-fallers is controversial, and has never been compared with fall risk assessment-specific tools, such as Performance-Oriented Mobility Assessment (POMA). Aim To verify the association of SPPB and POMA scores with falls in older outpatients. Methods 451 older subjects (150 males, mean age 82.1 ± 6.8) evaluated in a geriatric outpatient clinic for suspected frailty were enrolled in this cross-sectional study. Self-reported history of falls and medication history were carefully assessed. Each participant underwent comprehensive geriatric assessment, including SPPB, POMA, Geriatric Depression Scale (GDS), mini-mental state examination (MMSE) and mini-nutritional assessment-short form (MNA-SF). Multivariate logistic regression and receiver-operating characteristic (ROC) analyses were performed to determine the factors associated with the status of faller. Results 245 (54.3%) subjects were identified as fallers. They were older and had lower SPPB and POMA test scores than non-fallers. At ROC analysis, SPPB (AUC 0.676, 95% CI 0.627–0.728, p < 0.001) and POMA (AUC 0.677, 95% CI 0.627–0.726, p < 0.001) scores were both associated with falls. At multivariate logistic regression models, SPPB total score (OR 0.83, 95% CI 0.76–0.92, p < 0.001), POMA total score (OR 0.94, 95% CI 0.91–0.98, p = 0.002) and SPPB balance score alteration (OR 2.88, 95% CI 1.42–5.85, p = 0.004), but not POMA balance subscale score alteration, were independently associated with recorded falls, as also GDS, MMSE and MNA-SF scores. Conclusions SPPB total score was independently associated with reported falls in older outpatients, resulting non-inferior to POMA scale. The use of SPPB for fall risk assessment should be implemented.